2020
DOI: 10.1136/bmjopen-2020-040441
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalised COVID-19 patients of the Mount Sinai Health System: a retrospective observational study using the electronic medical records

Abstract: ObjectiveTo assess association of clinical features on COVID-19 patient outcomes.DesignRetrospective observational study using electronic medical record data.SettingFive member hospitals from the Mount Sinai Health System in New York City (NYC).Participants28 336 patients tested for SARS-CoV-2 from 24 February 2020 to 15 April 2020, including 6158 laboratory-confirmed COVID-19 cases.Main outcomes and measuresPositive test rates and in-hospital mortality were assessed for different racial groups. Among positive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 18 publications
(26 reference statements)
5
45
3
Order By: Relevance
“…To account for potential confounders, especially the age difference, we created a multivariate model where we adjusted for the effect of age, body mass index (BMI), gender, race, diabetes, HTN, chronic lung disease and heart disease on outcomes. Consistent with published literature( 49-52 ) (age and BMI were positively associated with COVID-19 severity and mortality (table S9. Using this multivariate model, we analyzed the impact of GI symptoms on disease outcomes.…”
Section: Resultssupporting
confidence: 90%
“…To account for potential confounders, especially the age difference, we created a multivariate model where we adjusted for the effect of age, body mass index (BMI), gender, race, diabetes, HTN, chronic lung disease and heart disease on outcomes. Consistent with published literature( 49-52 ) (age and BMI were positively associated with COVID-19 severity and mortality (table S9. Using this multivariate model, we analyzed the impact of GI symptoms on disease outcomes.…”
Section: Resultssupporting
confidence: 90%
“…Of the 85,328 adults tested for SARS-CoV-2, 9,971 (11.7%) were identified as Asian through a combination of EHR race and ethnicity data and surname matching. Of these, 4 Chronic diseases were prevalent among South Asians, who had a substantially higher rate of obesity (14.1% with BMI ≥30 and <40 and 1.7% with BMI ≥40), diabetes (23.1%), hypertension (26.0%), and heart disease (22.0%) than other Asian ethnic subgroups; these rates were comparable to and in some cases higher than those observed among Black and Hispanic patients.…”
Section: Characteristics Of Asian American Patientsmentioning
confidence: 84%
“…Evidence from NYC and the nation since that time, including from the Centers for Disease Control and Prevention (CDC), has shown that Blacks and Hispanics bear a substantially higher burden of COVID-19 than Whites, with Asian Americans reported as experiencing only a slightly higher burden than Whites. 2,3,4,5,6 However, community leaders and experts in Asian American health in NYC – which is home to the largest overall Asian and South Asian populations in the nation – and across the country have voiced concerns about the lack of attention to the substantial burden of COVID-19 among Asian Americans, many of whom have similar clinical, social, and economic characteristics as other Americans of color. 7,8,9,10 This is due in large part to two key factors: 1) an undercount of Asian Americans in health system records because of inadequate or inaccurate data collection and reporting of Asian Americans’ race and/or ethnicity (i.e., as “other,” “unknown,” or an incorrect race, e.g., American Indian/Native American race instead of Asian race and Indian ethnicity), and 2) aggregating all Asian ethnic groups into a single race category, thereby obscuring differences in characteristics and outcomes between these diverse groups.…”
mentioning
confidence: 99%
“…BACC (USA) [ 19 ] and RCT-TCZ-COVID-19 (Italy) [ 21 ] reported 3.3 and 2.4% mortality respectively. Whereas reported mortality for hospitalized Covid-19 patients in USA [ 25 ] and Italy [ 26 ] is 22.6 and 29.7% respectively, implying thereby that these RCTs enrolled mild cases of Covid-19 for tocilizumab usage.…”
Section: Discussionmentioning
confidence: 99%